A Preliminary Investigation of Disease of Bamboo in North-east Region of India - Deka, P. C.; Baruah, Gayatri; Mala Devi, (Indian Forester, 1990)
Disease occurred in different bamboo species of Nortb-East India were recorded and identified. Various symptoms related to the specific disease were studied. Gray leaf spot of Bambusa nutans caused by Hendersonula toruloidea, Brown leaf spot of Melocanna humilis and Fusarium leaf spot of Teinmtachyum dullooa caused by Fusarium pallidoroseum and Chlorosis of Dendrocalamus hamiltonii caused by Paecilomyces hlacinus bas been identified and studied.